Answer:
See below
Explanation:
![(d)/(dx) (\tan^3 x) = 3\sec^4 x - 3\sec^2 x](https://img.qammunity.org/2023/formulas/mathematics/college/j2xqk88r9u8oi8yuwd112pagfi891balpy.png)
Recall
![(d)/(dx)\tan x=\sec^2](https://img.qammunity.org/2023/formulas/mathematics/college/71x51m0dj2ujnnrtrazlib98nz693b9oj1.png)
Using the chain rule
![(dy)/(dx)= (dy)/(du) (du)/(dx)](https://img.qammunity.org/2023/formulas/mathematics/college/yc09pddv4db8rwjewjoz7zjr0dgnqdm74a.png)
such that
![u = \tan x](https://img.qammunity.org/2023/formulas/mathematics/college/wrfjtcm4l8elbzjnils68hvnn27fdqwe1u.png)
we can get a general formulation for
![y = \tan^n x](https://img.qammunity.org/2023/formulas/mathematics/college/80vmjkscp8i8v6tnmrr98ggs3j3e85pfvq.png)
Considering the power rule
![\boxed{(d)/(dx) x^n = nx^(n-1)}](https://img.qammunity.org/2023/formulas/mathematics/college/b6n7p33cry39k56m775n96aocm2w6v3xtf.png)
we have
![(dy)/(dx) =n u^(n-1) \sec^2 x \implies (dy)/(dx) =n \tan^(n-1) \sec^2 x](https://img.qammunity.org/2023/formulas/mathematics/college/gurtds7qh5oaub0q0ox6814il0myijt66z.png)
therefore,
![(d)/(dx)\tan^3 x=3\tan^2x \sec^2x](https://img.qammunity.org/2023/formulas/mathematics/college/wv1n2np30v39mcxg4tn2npbnius2k3ojqe.png)
Now, once
![\sec^2 x - 1= \tan^2x](https://img.qammunity.org/2023/formulas/mathematics/college/rb2ihbhy8fqm5fs2wijmul92ho97nxdive.png)
we have
![3\tan^2x \sec^2x = 3(\sec^2 x - 1) \sec^2x = 3\sec^4x-3\sec^2x](https://img.qammunity.org/2023/formulas/mathematics/college/8qu5i2jtudkjpkpfq8zmah6iqkc7j61rwe.png)
Hence, we showed
![(d)/(dx) (\tan^3 x) = 3\sec^4 x - 3\sec^2 x](https://img.qammunity.org/2023/formulas/mathematics/college/j2xqk88r9u8oi8yuwd112pagfi891balpy.png)
================================================
For the integration,
![$\int \sec^4 x\, dx $](https://img.qammunity.org/2023/formulas/mathematics/college/b2qidzmot41zbmg6wu8i67sm9cmbre3xxw.png)
considering the previous part, we will use the identity
![\boxed{\sec^2 x - 1= \tan^2x}](https://img.qammunity.org/2023/formulas/mathematics/college/yeg568040y8mhrtjek4bpb4apl93h23m6n.png)
thus
![$\int\sec^4x\,dx=\int \sec^2 x(\tan^2x+1)\,dx = \int \sec^2 x \tan^2x+\sec^2 x\,dx$](https://img.qammunity.org/2023/formulas/mathematics/college/y7vvfdh3cogqx58hxgnv5j8eutfbalbzbn.png)
and
![$\int \sec^2 x \tan^2x+\sec^2 x\,dx = \int \sec^2 x \tan^2x\,dx + \int \sec^2 x\,dx $](https://img.qammunity.org/2023/formulas/mathematics/college/x0w8oobz0o5hw5qfiuyi4zkx24boivq5cd.png)
Considering
![u = \tan x](https://img.qammunity.org/2023/formulas/mathematics/college/wrfjtcm4l8elbzjnils68hvnn27fdqwe1u.png)
and then
![du=\sec^2x\ dx](https://img.qammunity.org/2023/formulas/mathematics/college/51nbrwpzwqqoqsbp5kvd6qyfrzwbendepq.png)
we have
![$\int u^2 \, du = (u^3)/(3)+C$](https://img.qammunity.org/2023/formulas/mathematics/college/rx5hauj99abfy0gd2h3ebpn2axfi0dpy0z.png)
Therefore,
![$\int \sec^2 x \tan^2x\,dx + \int \sec^2 x\,dx = (\tan^3 x)/(3)+\tan x + C$](https://img.qammunity.org/2023/formulas/mathematics/college/qmcwshc05tl4lgjdi71a762fjhycfbbvgy.png)
![$\boxed{\int \sec^4 x\, dx = (\tan^3 x)/(3)+\tan x + C }$](https://img.qammunity.org/2023/formulas/mathematics/college/41o595k3r5rdxjoj614pj489ivlrgmc82e.png)